Nonsense-mediated and Staufen1-mediated mRNA decay: related pathways of post-transcriptional control in mammalian cells - Maquat, Lynne (Henry Stewart Talks, 2007)
Three core Upf NMD factors, Exon junction complexes (EJCs), Upf1, Mechanism of NMD, Activation of EJC-bound Upf1, Role of NMD in downregulating spliced mRNAs to eliminate truncated proteins, NMD downregulating functional protein isoforms, Restriction to newly synthesized mRNAs during a pioneer round of translation, Cap Binding Protein (CBP) heterodimer CBP80-CBP20, Eukaryotic translation initiation factor (eIF) 4E and steady state mRNA, Role of CBP80 in enhancing efficiency of NMD by promoting the interaction of Upf1 with EJC-bound Upf2, Staufen (Stau)1-mediated mRNA decay (SMD), Double-stranded RNA binding protein Stau1, Mechanism of action of SMD
Reviewed at 2016/01/07